KauAku: Interpretation of Toxic Relationships and Senandung Jolo - Mirnawati Mirnawati; Asril Asril (Universitas Negeri Medan, 2023)
Toxic relationships are dangerous. Toxic relationships are often found in dating relationships. The cause of a toxic relationship is when in a relationship there is intimidating behavior towards their partner, being rude, reluctant to blame and winning alone. The social phenomena of toxic relationships or toxic relationships above become ideas in the creation of works. The creators interpret the atmosphere and emotions experienced in dating such as joy, sadness, anger, chaos and moral messages about dating as important parts that can be expressed. In developing the work, the artist uses the local idiom of the Senandung Jolo tradition. The creation method used in the cultivation is based on the testimony of the creative thinker Graham Wallas (1926) in the book Psychology of Art by Irma Damayanti it is stated that there are three stages, namely the data collection stage, the observation stage, and the work embodiment stage. The author interprets that a toxic relationship always begins with harmony, but there is also an emotional imbalance with the big title Composition KauAku, which consists of three works entitled